DOP26 Biological therapy increases NCR+ ILC3 levels in IBD patients. (25th January 2019) - Creyns, B; Verstockt, B; Cremer, J; Ballet, V; Ferrante, M; Vermeire, S; Ceuppens, J; Van Assche, G; Breynaert, C
Abstract: Background: Innate lymphoid cells (ILCs) reside at mucosal barriers where they exhibit high cytokine producing capacity to maintain homeostasis and control infections. Natural cytotoxicity receptor (NCR) positive ILC3s, an important source of intestinal IL-22, have been shown to be decreased in the mucosa of patients with Crohn's disease (CD) and ulcerative colitis (UC) in favour of pro-inflammatory ILC1s. To study whether current biological anti-TNF, ustekinumab (UST) or vedolizumab (VDZ) therapy can restore the intestinal ILC balance, ILC frequencies were determined in serial blood and biopsies samples. Methods: We included 26 CD patients initiating UST, 14 patients initiating VDZ (9 CD, 5 UC), 14 CD patients initiating anti-TNF (8 infliximab, 6 adalimumab) and 10 healthy controls (HC) without endoscopic abnormalities. All cohorts were matched for age, gender, and age at diagnosis. Colonic biopsies and blood were taken at baseline and during endoscopic assessment (Week 8–14 UC, 24 CD). Peripheral blood and lamina propria mononuclear cells were stained for flow cytometric analysis. Pairwise comparisons were performed on ILC numbers determined as frequency of total ILC or total leucocyte population. Results: Intestinal NCR+ ILC3 levels before initiation of biological treatment were significantly decreased in anti-TNF and VDZ cohort (42.0, 37.5 vs. 86.8% of total ILC, both p < 0.001) while ILC1 levels were increased (15.7, 7.7 vs. 2.7, both p < 0.01) when compared with HC. In contrast, ILC subgroup levels were not different in the UST cohort (NCR+ ILC3: 74.8, ILC1:2.4, p = 0.9). In the anti-TNF and VDZ cohort, recovery of NCR+ ILC3s compared with start ( p = 0.04, p = 0.03) was observed after first endoscopic evaluation independent of treatment response. Mucosal ILC levels could not be correlated to peripheral ILC levels ( r = 0.39, p = 0.27); however, an increase of peripheral NCR+ ILC3s in the total ILC (Figure 1) and leucocyte population could be observed in both the anti-TNF ( p = 0.01) and UST ( p = 0.001) cohort when compared with the start of therapy. In contrast, no effect of VDZ ( p = 0.47) was observed on peripheral ILC levels. Conclusions: Biological therapy can restore the intestinal ILC levels towards homeostatic proportions even in absence of endoscopic response. Anti-TNF and UST treatment increased NCR+ ILC3s levels in the circulation, which are not described in physiological conditions. In contrast, no increased NCR+ ILC3s levels were not observed in VDZ-treated patients. NCR+ ILC3 level will be correlated to cytokine levels in future.